Redescription of Echinocoleus hydrochoeri (TRAVASSOS, 1916) (NEMATODA: TRICHURIDAE) from Hydrochoeris hydrochaeris LINNAEUS, 1766 (RODENTIA: CAVIIDAE) from Argentina - Robles, Maria del Rosario (2013)
Twenty-eight Capillariinae species have been recorded in rodents; 1 of these was reported from a caviomorph rodent, Hydrochoeris hydrochaeris, and placed in the genus Echinocoleus by Moravec (1982). However, both original description and subsequent contributions of Echinocoleus hydrochoeri are poor and incomplete. In this paper, this species is redescribed, and a new geographical distribution is reported. The redescription is based on morphologic and morphometrical features; intestine ends in a cloaca beside ejaculatory duct, caudal bursa composed of 2 large ventrolateral lobes with a fleshy internal part and a membranous external part (they are not united dorsally with a membrane), 1 pair of caudal papillae, terminal part of cylindrical cirrus ornamented with thin and thick spines (and particular pattern distribution), sclerotized spicule in male, and vulvar appendage in female, and 3 bacillary bands (1 ventral and 2 lateral). Generic and specific analyses were performed in order to establish new standards for future studies on the systematic position of Capillariinae species. This study presents new morphological information and a new record of a capillariid species from Argentina.